Suitability of chlorhexidine impregnated dressings on dialysis catheters in an acute dialysis setting: Lessons from our experience - Zimbudzi, Edward (International Journal of Infection Control, 2012)
Haemodialysis Catheter-Related Infections (HCRIs) are a major cause of mortality and morbidity among the dialysis population and they have also overburdened the health care systems financially. Due to this problem, many dialysis units are keen to implement any evidence-based procedure that could reduce the occurrence of HCRIs. One such procedure is the dressing of haemodialysis permacath exit sites. The purpose of this study was to find out if there were any significant benefits of using chlorhexidine impregnated patches (biopatch™) to dress permacath exit sites in an acute dialysis setting of a metropolitan teaching hospital.Utilizing an observational longitudinal study design, fourteen participants with permacaths were conveniently sampled. Permacaths sites were dressed with biopatch dressings which were changed after every 7 days and more often if the exit site showed signs of redness or bleeding. Post biopatch trial, all the patients who participated in this trial were followed up for three months. During the follow up period, permacaths exit sites were cleaned with chlorhexidine 2% and then mupirocin (bactroban) ointment was applied as per unit’s protocol followed by an application of an IV 3000 dressing to cover the exit site. The dressing was changed three times a week.Bleeding of catheter site resulted in removal of 19% of the dressings before the standard 7 day period and 37% of the patches were changed prematurely due to suspected exit site infection. Only 2% of the patches were taken off due to exit site sensitivity to the biopatch™. There were 15 patches (35%) which were removed after 7 days and 7% of the patches were not followed up. Overall, dressings were left intact for a mean period of 4.8 days SD ±1.8. One case of suspected CABSI was reported during the three months post biopatch use.The results of this trial demonstrate that using biopatch™ in an acute dialysis unit may not produce anticipated positive results to the patient and the economic benefit to the health service may be minimal.